"Complete illustrated guide to islam / by Raana Bokhari, Mohammad Seddon and Charles Phillips" - "Bokhari, Raana" (London, 2009)
In the contemporary world the Islamic community is represented by around 1.4 billion people or twenty-five percent of the global population, from a wide range of ethnic, national linguistic, theological, political and socioeconomic backgrounds. This book comprehensively explores the life and work of Muhammad, the history of Islam, Islamic beliefs and doctrine, and religious practices and worship. Beautifully illustrated with more than 500 fine-art paintings, artworks, maps and photographs, and including a helpful timeline, it offers a comprehensive introduction to and overview of a complex and often misunderstood religion.
Keywords: Islam